Batasan Kedewasaan dan Kecakapan Hukum Pewasiat Menurut Kompilasi Hukum Islam dan Kitab Undang-Undang Hukum Perdata - Sanawiah Sanawiah; Muhammad Zainul (Jurnal Hadratul Madaniyah, 2018)
Limitations of adulthood and lawfulness of the pewasiat both in terms of the position of limits and the ability of the pewasiat, the requirements of the pewasiat and the various limits of the age of the pewasiat according to different views and opinions among the Imam of the School in the determination of its law. The purpose of this study is to to assess the Limitations of adulthood and legal proficiency of pewasiat by Compilation of Islamic Law and Civil Code contained in the Compilation of Islamic Law Article 194 paragraph 1 and Book Civil Law Article 897. In Compilation of Islamic Law Article 194 paragraph 1 concerning the will specifies that the person who intends to reach the age of 21 full and sensible this is a requirement for mlekukan wills must reach the age that has been determined. The Civil Code states that in Article 897 it states that the person who intentions must reach the age of 18 full years, this is a condition of determination to perform the testament. Normative legal research methods analyze, related legislation presented through descriptive and deductive methods which are then analyzed to see the location of similarities and differences between the Compilation of Islamic Law and the Civil Code. The result of this research is the equation of Law Compilation of Compilation of Islamic Law and Civil Code which states the condition of the person having the will should be sensible, while in the determination of maturity 21 years based on article 330 Civil Code. As for the legal proof of Article 426 Civil Code aged 18 years.